Augmented Reality : Media Pembelajaran pada Mata Kuliah Fisika Lingkungan - Siringo Ringo, Indah Kristiani; Rahman, Nurdin Abd; Sarina, Sarina (Tolis Ilmiah : Jurnal Penelitian, 2025)
Rapid advances in digital technology have significantly transformed higher education, particularly in how students construct understanding of abstract scientific concepts. Among recent innovations, Augmented Reality (AR) has gained prominence for its ability to present three-dimensional visualizations of physical phenomena that are otherwise invisible in real-world observation. This study investigates the effect of AR-based learning media on students’ learning outcomes in the Environmental Physics course. A quantitative pre-experimental design of the one-group pretest–posttest type was implemented with 15 Physics Education students who participated in learning activities utilizing AR media. Data on learning performance were collected through pre- and post-tests, analyzed for normality, and further examined using a paired-sample t-test to determine the significance of differences in learning outcomes. The findings revealed an increase in the mean learning score from 55.56 (pretest) to 72.33 (posttest), with a significance value of p = 0.000 < 0.05, confirming a statistically meaningful improvement after the intervention. The results indicate that AR effectively enhances students’ conceptual comprehension, promotes learning motivation, stimulates active engagement, and strengthens critical-thinking ability during the learning process. In conclusion, Augmented Reality represents an innovative and effective pedagogical medium for improving both the quality of instruction and conceptual mastery, particularly in courses demanding high levels of abstract visualization such as Environmental Physics. Future research should involve larger and more diverse samples and explore AR integration across other scientific disciplines to obtain broader empirical insights.